Fitoremediasi Logam Aluminium (Al) Pada Lumpur Instalasi Pengolahan Air Menggunakan Tanaman Melati Air (Echinodorus palaefolius) - Monik Kasman; Anggrika Riyanti; Catur Endah Kartikawati (Jurnal Daur Lingkungan, 2019)
Clean water as basic need produced by the Regional Water Company (PDAM) and the by-product of this production was in the form of sludge.  PDAM sludge contain Aluminium in the form of Al (OH)3 with the potential pollution if thrown into environment. This research aims to determine the efficiency of removal of Al metal on PDAM sludge through phytoremediation by using jasmine water plants and to determine  the absorption of Al metal that accumulates in the roots of water jasmine plants in phytoremediation I (without media) and phytoremediation II  (with gravel and humus soil). Sludge sample was carried out directly on the outlet sludge drying bed PDAM Water Treatment Plant (IPA) Tanjung Sari. The phytoremediation process is then carried out to reducted Al metal content in the sludge by using water jasmine plants. Furthermore, Al metal concentrations were analyzed at 3, 5, 7, 9 and 11 days of contact and analysis of Al metal absorption on the roots of jasmine water plants was done after phytoremediation process in days-11. The result showed at the contact time 3, 5, 7, 9, and 11 day, the efficiency of Al metal concentration on the phytoremediation I in a sequence were 46%; 62%; 72%; 80%; and 83%, while in phytoremediation II were 50%; 67%; 75%; 81%; and 86%. The concentration of Al metal absorption on the roots of jasmine plant water at phytoremediation I and phytoremediation II are 898,10 mg/l dan 302,42 mg/l. The high absorption in the phytoremediation I due to the absence of planting media so the metal occurs more optimal but they really experienced low power regeneration. While in phytoremediation II which has a growing media, formed a rizosfer zone which is rich in oxygen and microorganism so that the plant having a higher level of regeneration.